Development of refrigeration and heat pump systems - Pearson, Andy (Frontiers in Thermal Engineering, 2022)
Despite continual development over more than two centuries there is still great scope for significant development in the realms of mechanical cooling and heating. This paper reviews the nature of the historical development and identifies key motivations for technical development. It seeks to highlight where there is greatest need for future development in this ubiquitous technology. The story of the development of mechanical refrigeration is dominated by the choices made with regard to the working fluid used in the system. These choices dictate the operating parameters of temperature and pressure that the system must withstand as well as introducing constraints related to material compatibility, so the agenda for the mechanical development of systems is set by the selection of the refrigerant. All of these systems are classed as heat pumps because they extract heat from one location and deliver it to another. The commercial demand for mechanical cooling in the 19th century meant that all of these early heat pump systems were used for cooling. The concept of using the same cycle to deliver useful heat was not commercialised until the mid-twentieth century and in some ways this application of the heat pump is still in the early stages of development, particularly with regard to market penetration.